Synthesis retinal analogues of spiropyran derivaties, investigation they interactions with bacteriorhodopsin from H. salinarum - A. V. Laptev; A. Yu. Lukin; A. A. Khodonov (Тонкие химические технологии, 2006)
The opportunity of design of analogue retinal with replacement of trimethylhexenic ring of a molecule on spiropyran moiety is shown. Process of interaction of the synthesized retinal analogues with bacterioopsin from apomembrane Halobacterium salinarum and their spectral propertie of formed pigments is investigated